“ENCARANDO A MODERNIDADE E ACOMPANHANDO A TENDÊNCIA”: UMA ANÁLISE DAS REPRESENTAÇÕES DE GÊNERO PRESENTES NA REVISTA BATISTA VISÃO MISSIONÁRIA NO PERÍODO DE 1975 A 2015 - AMANCIO, ELIANA APARECIDA (2018)
Visão Missionária magazine was founded in 1922 in order toteach Baptist women how to hold their meetings as well as to prepare single Baptist women to become missionaries and pastors’ wives. As time moves on, the model of traditional mission is no longer the main topic of the magazine, which started creating other models of missions. The fight against social injustice, discrimination, violence, oppression and other topics were part of those new models. Therefore, the magazine added to its pages stories that would invitewomen to think about their daily lives. Due to these changes, new gender representations have been built in the magazine profile. Our study pointed out, analyzed and compared gender representations with new meanings as well as those maintained by the magazine. Temporal limitation is of forty years, divided into three periods: 1975, 1995, and 2015. We applied Content Analysis and Discourse Analysis, and realized that gender representations in the 1975 contents are kept, but with a few change. Concerning years 1995 and 2015, although traditional representations are kept, the new meanings of gender representations are present in most part of the contents.Women and men negotiate and/or adapt traditional gender representations to the new ones, which gives them opportunities to find new meanings to their lives.